Training on the Use of the Independent Teaching Platform for Elementary School Teachers - Erni, Erni; Supriadi, Supriadi; Usman, Usman; Rusti, Rusti (Jurnal IPMAS, 2023)
Platform Merdeka Mengajar (PMM) is a form of work technology advancement that makes it easier for internal teachers to teach, learn and be creative. Teachers can get references, inspiration and understanding in implementing the Independent Teaching Curriculum. This morning app is very useful for driving teachers. In fact, there are many teachers who still can't even access the application even though they already have an ID (special teacher ID). The aim of this service is to provide socialization and training on the use of the Merdeka Mengajar Platform as well as providing socialization and understanding of the Pancasila P5 Profile to PSP 3 Elementary School Teachers, Sidrap Regency. The methods of devotion are gaze, face and presentation. The target of the activity is the teachers of the Sidrap Regency Education Service. After the activity, the teachers understood and recognized the benefits of using the Merdeka Mengajar Platform and felt the benefits of the P5 Pancasila knowledge material